EVALUATION OF ANTIMICROBIAL AND ANTIOXIDANT ACTIVITY OF ISOLATED CONSTITUENTS FROM AREAL PART OF CUSCUTA REFLEXA ROXB. PLANT - Sandeep; Mittal, Abhilasha (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Â Objective: The objective of the study was to investigate the pharmacological evaluation of previously isolated compounds (CR-1 to CR-5) from the areal part of Cuscuta reflexa Roxb. is reported. Methods: The antimicrobial and antioxidant activity of the isolated compounds (CR-1 to CR-5) from C. reflexa was determined by the disc-diffusion method and 1,1-diphenyl-2-picryl-hydrazyl (DPPH) model, respectively. The antimicrobial activity was performed against four strains Staphylococcus aureus, Bacillus subtilis, Escherichia coli, and Pseudomonas aeruginosa. Results: The results revealed that highest zone of inhibition is measured by compound CR-5 against E. coli. The antioxidant activity is evaluated for in vitro antioxidant activity using DPPH radical scavenging activity, inhibitory concentration 50% (IC50) (120.92â€“76.38 %), respectively. The results indicate that isolated compound CR-1 and CR-2 having IC50 76.38 and 76.94 Î¼g/ml, respectively, showed potent antioxidant activity comparable to standard ascorbic acid (IC50 43.42 Î¼g/ml). Conclusion: This study suggests that areal part of C. reflexa have bioactive compounds for a new antimicrobial and antioxidant drug development.